If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8x + -8) + -1(6x + -10) = 0 Reorder the terms: (-8 + 8x) + -1(6x + -10) = 0 Remove parenthesis around (-8 + 8x) -8 + 8x + -1(6x + -10) = 0 Reorder the terms: -8 + 8x + -1(-10 + 6x) = 0 -8 + 8x + (-10 * -1 + 6x * -1) = 0 -8 + 8x + (10 + -6x) = 0 Reorder the terms: -8 + 10 + 8x + -6x = 0 Combine like terms: -8 + 10 = 2 2 + 8x + -6x = 0 Combine like terms: 8x + -6x = 2x 2 + 2x = 0 Solving 2 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 2x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 2x = 0 + -2 2x = 0 + -2 Combine like terms: 0 + -2 = -2 2x = -2 Divide each side by '2'. x = -1 Simplifying x = -1
| 4x=-(3/16) | | 4/x+7/x^2-2/x^3 | | 8x-8-6x-10= | | =3z(8-5z) | | 6x-4+5x+3= | | 9+3ab+-1ab+-4=0 | | -6(5x-3y+4)= | | 3xh+9x= | | y=3x^2-x+20 | | 5(6-5k)=30 | | 5(d-7)+12= | | 4r+3.4-4.6r-4.7r-3= | | 10x+15=6x+59 | | 7x-3x+2x-6+5x= | | 11x^6+121x^2-44x^4= | | 3x-9=4x-25 | | 6.5x-3+5x-2.1= | | 10x-72=6x-12 | | n/200+n/100 | | n/200+n/100=80-50 | | (2x+1)(2x+1)=x+11 | | 17-3g=3-g | | 2(t^2-3t+4)=0 | | 2(5x-4)=18 | | -5=-2x-12 | | 3x^2+8x+2=2x+26 | | 8/14 | | x^2+3x=(3x-15) | | x^2+3x=3x-15 | | 5x^2+7x+8= | | 2r-5p=32 | | 0=x^2-4x-24 |